C-2 derivatized 8-sulfonamidoquinolines as antibacterial compounds. (1st January 2021) - Davison, Emma K.; McGowan, John E.; Li, Freda F.; Harper, Andrew D.; Jeong, Joo Young; Mros, Sonya; Harbison-Price, Nichaela; Van Zuylen, Essie M.; Knottenbelt, Melanie K.; Heikal, Adam; Ferguson, Scott A.; McConnell, Michelle A.; et al.
Graphical abstract: Abstract: A series of C-2 derivatized 8-sulfonamidoquinolines were evaluated for their antibacterial activity against the common mastitis causative pathogens Streptococcus uberis, Staphylococcus aureus and Escherichia coli, both in the presence and absence of supplementary zinc (50 µM ZnSO4 ). The vast majority of compounds tested were demonstrated to be significantly more active against S. uberis when in the presence of supplementary zinc (MICs as low as 0.125 µg/mL were observed in the presence of 50 µM ZnSO4 ). Compounds 5, 34 –36, 39, 58, 79, 82, 94 and 95 were shown to display the greatest antibacterial activity against S. aureus (MIC ≤ 8 µg/mL; both in the presence and absence of supplementary zinc), while compounds 56, 58 and 66 were demonstrated to also exhibit activity against E. coli (MIC ≤ 16 µg/mL; under all conditions). Compounds 56, 58 and 66 were subsequently confirmed to be bactericidal against all three mastitis pathogens studied, with MBCs (≥3log10 CFU/mL reduction) of ≤ 32 µg/mL (in both the presence and absence of 50 µM ZnSO4 ). To validate the sanitizing activity of compounds 56, 58 and 66, a quantitative suspension disinfection (sanitizer) test was performed. Sanitizing activity (>5log10 CFU/mL reduction in 5 min) was observed against both S. uberis and E. coli at compound concentrations as low as 1 mg/mL (compounds 56, 58 and 66 ), and against S. aureus at 1 mg/mL (compound 58 ); thereby validating the potential of compounds 56, 58 and 66 to function as topical sanitizers designed explicitly for use in non-human applications.